Evaluation of learning resource rooms in public schools in Ajloun governorate in puplic school in Ajloun governorate in accordance to teachers point of view - Al-Jabali, Ahmad Ali (Journal of Educational and Psychological Sciences, 2020)
This study aims at identifying the evaluation of learning resources rooms in public schools in Ajloun governorate from the point of view of their teachers. The study was based on the descriptive analytical method. The study population consisted of (107) male and female teachers. random. The study reached a set of results, The most important: The arithmetic averages of the responses of the study sample to evaluate the room of learning resources as a whole came with a high degree, with an average of (3.63) and the field of parents with a high degree, and an arithmetic average (3.92), followed by the teacher field, with an average (3.66). ), Then the student field, with an average (3.64), while the resource room field, the lowest average score, with an average (3.40), The results also showed that there is no statistically significant difference according to sex and educational qualification, and that there are statistically significant difference for the job experience variable for (11 years and above). To disseminate the experience of forming a support committee to all departments, institutions and programs working with people with special needs in the local community.